1997
DOI: 10.1038/sj.leu.2400542
|View full text |Cite
|
Sign up to set email alerts
|

The use of monoclonal gene rearrangement for detection of minimal residual disease in acute lymphoblastic leukemia of childhood

Abstract: Sensitive quantification of minimal residual disease (MRD)cells requiring to be eliminated, and, when measured late in using the polymerase chain reaction (PCR) is strongly predicthe disease, the level of MRD may provide evidence for tive of outcome in childhood acute lymphoblastic leukemia impending relapse. MRD can be detected in a proportion of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
2
18
0
Order By: Relevance
“…Simplified techniques using standard PCR, 40,41 RQ-PCR 42 or GeneScan 43,44 have proven to be valid for the study of MRD in ALL. Recently, a simplified and relatively inexpensive technique of MRD detection on day 19 of induction therapy by flow cytometry using a panel of only three monoclonal antibodies was able to identify children with B-lineage ALL with a very good response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Simplified techniques using standard PCR, 40,41 RQ-PCR 42 or GeneScan 43,44 have proven to be valid for the study of MRD in ALL. Recently, a simplified and relatively inexpensive technique of MRD detection on day 19 of induction therapy by flow cytometry using a panel of only three monoclonal antibodies was able to identify children with B-lineage ALL with a very good response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Sensitivities of around 5% are clinically relevant for initial diagnosis, but they are certainly not sufficient for detection of minimal residual disease (MRD) in ALL patients which requires sensitivities of 10 −4 to 10 −5 . 35 It has been suggested that sensitivities of 10 −2 to 10 −3 as determined by PCR might be predictive for slow remission upon chemotherapy, 36 but such sensitivities cannot easily be reached via heteroduplex analysis of PCR products, unless most of the polyclonal T cells are depleted before DNA or RNA extraction. Nevertheless, heteroduplex PCR analysis of TCR gene rearrangements is sufficiently sensitive for monitoring patients with chronic T cell leukemias as well as patients with oligoclonal T cell proliferations in order to predict the possible outgrowth of a dominant cell population.…”
Section: Figurementioning
confidence: 99%
“…10,15,16 PCR products were separated by polyacrylamide gel electrophoresis and examined visually under UV light after staining with ethidium bromide. Monoclonality (or oligoclonality) was defined by the presence on electrophoresis of one (or several) homogeneous PCR products which were identical in both duplicates.…”
Section: Detection Of Monoclonalitymentioning
confidence: 99%
“…At the one extreme, there are simple techniques, such as detection of a monoclonal gene rearrangement using consensus primers, which is non-quantitative and is capable of detecting leukemia down to a level of approximately 10 −3 . 10,11 At the other extreme, there is detection of a monoclonal gene rearrangement using two clone-specific primers which, together with a sensitive quantitation method such as limiting dilution analysis, 12 is capable of accurate quantitation probably down to 10 −5 to 10 −6 . In between there are several methods of intermediate complexity, in which some specificity for the leukemic clone is obtained by specific probing or use of a single specific primer, and which are more quantitative or less quantitative, depending on the exact detection technique used.…”
Section: Introductionmentioning
confidence: 99%